P1654INCIDENCE AND RISK FACTORS OF THROMBOTIC MICROANGIOPATHY AFTER KIDNEY TRANSPLANTATION - Futamura, Kenta; Norihiko, Goto; Fukuhara, Hiroki; Nawano, Takaaki; Kanda, Akiko; Tomosugi, Toshihide; OKADA, Manabu; Tsujita, Makoto; HIRAMITSU, Takahisa; Narumi, Shunji; Watarai, Yoshihiko (Nephrology Dialysis Transplantation, 2020)
Abstract Background and Aims Thrombotic microangiopathy (TMA) is characterized by mechanical hemolytic anemia, thrombocytopenia, and renal impairment. TMA that occurs in kidney transplant recipients has multiple etiologies and may be de novo or recurrent. Main causes of TMA among recipients are atypical hemolytic uremic syndrome (aHUS), immunosuppressive drugs, ischemia-reperfusion injury (IRI), viral infections, and antibody-mediated rejection (ABMR). Pathological findings of TMA with thrombosis in glomeruli and arterioles are not rare in graft biopsies, but the clinical signs vary widely by etiologies, and incidence and risk factors for each are uncertain. The purpose of this study is to clarify the current status of TMA after kidney transplantation. Method The subjects were 1,336 patients (5,425 biopsy specimens) who underwent kidney transplantation (851 ABO-compatible and 485 ABO-incompatible) at Japanese Red Cross Nagoya Daini Hospital and Masuko Memorial Hospital from January 1, 2000 to June 30, 2018. We investigated patient characteristics and graft survival in 69 patients with pathological findings of TMA (12 with symptomatic TMA and 57 with asymptomatic TMA) and 1,207 patients without findings of TMA. Sixty patients were excluded because of incomplete data or biopsy specimens. TMA patients with acute kidney injury (AKI) were defined as symptomatic TMA in this study. Results The incidence of post-transplant TMA was 5.2% (symptomatic TMA : 0.9%, asymptomatic TMA : 4.3%) in our cohort. Multivariate analysis revealed significant risk factors for TMA were presence of donor specific antibodies (DSA) and use of cyclosporine (odds ratio [OR] 3.52; 95% confidence interval [CI] 1.58-7.88; p=0.002 and OR 3.70; 95% CI 1.68-8.11; p=0.001, respectively). Causes of symptomatic TMA were ABMR : 66.7% (5 patients with ABO-incompatibility, 3 with preformed DSA), aHUS : 16.7%, cytomegalovirus and adenovirus infection : 8.3%, and causes of asymptomatic TMA were drug-induced: 40.4% (21 patients with calcineurin inhibitor, 2 with everolimus), ABMR: 31.6% (10 with ABO-incompatibility, 8 with de novo DSA), IRI : 14.0 %. Onset of post-transplant TMA was significantly associated with lower graft survival (Figure A), with a stronger correlation in symptomatic TMA than in asymptomatic TMA (Figure B and C). Conclusion TMA with AKI that occurred after kidney transplantation had a poor graft prognosis. Therefore, avoiding transplantation, changing donors or using tacrolimus instead of cyclosporine should be considered for patients with DSA or ABO-incompatibility. Figure: